Implementasi Akuntabilitas dan Transparansi Zakat: Pengembangan Sumber Daya Manusia di Lembaga Amil Zakat Rumah Peduli Nurul Fikri - Thahir, A. Halil; Tohari, Ilham; Abd. Rahman, Zayad (Management of Zakat and Waqf Journal (MAZAWA), 2021)
The Nurul Fikri Care House Amil Zakat Institution is a manifestation of the Institution-based Zakat Management Act established by the community as a way of incubating poverty and providing muzakki in distributing zakat. Rumah Peduli Nurul Fikri is the original form of an organization with a modern concept by prioritizing the basis of accountability and transparency in collecting, collecting, and distributing zakat, which is in Law number 23 article 17 of 2011 concerning Zakat Management to realize the first goal of zakat as a way of welfare of Muslims. The accountability of the amil zakat institution, Rumah Peduli Nurul Fikri, is known for containing the law and also includes the principles of accountability for zakat management, namely based on Islamic law, trustworthiness, expediency, justice, legal certainty, integrity, and accountability. This is the satisfaction of legal compliance in Law Number 23 article 2 of 2011 concerning Zakat Management. The transparency of the amil zakat institution, Rumah Peduli Nurul Fikri, is respected in the management of zakat funds through transparency of information and administrative reporting to authorized bureaus that participate in zakat management. openness to the amil zakat institution, Rumah Peduli Nurul Fikri, which is revealed in the management of zakat through the implementation of activities and information that can be carried out in general.